Normalization in World Politics - Lemay-Hebert, Nicolas (University of Michigan Press, 2022)
As we face new challenges from climate change and the rise of populism in Western politics and beyond, there is little doubt that we are entering a new configuration of world politics. Driven by nostalgia for past certainties or fear of what is coming next, references to normalcy have been creeping into political discourse, with people either vying for a return to a past normalcy  or coping with the new normal. This book traces main discourses and practices associated with normalcy in world politics. Visoka and Lemay-Hébert mostly focus on how dominant states and international organizations try to manage global affairs through imposing normalcy over fragile states, restoring normalcy over disaster-affected states, and accepting normalcy over suppressive states. They show how discourses and practices come together in constituting normalization interventions and how in turn they play in shaping the dynamics of continuity and change in world politics.